The Importance of Digital Technologies in Elementary Mother Tongue and Reading Literacy Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes the importance of digital technologies in the course of the lesson, the effectiveness and useful aspects of mutual integration of subjects. It is said that connecting not only several subjects, but also topics within the subjects will be highly effective and motivate students to be interested in the lesson.